Correlated neurocardiologic and fitness changes in athletes interrupting training - Frederiks, J.; Swenne, C. A.; Bruschke, A. V.; Van der Velde, E. T.; Maan, A. C.; Tenvoorde, B. J.; Vanrooijen, M. G.; Mosterd, W. L.; Schiereck, P. (Medicine & Science in Sports & Exercise, 2000)
Purpose: We studied nine male Dutch top marathon skaters during a 1-month interruption of their training schedules after their last contest in the winter to investigate a possible decline in baroreflex sensitivity. Methods: Before and after this period, a maximal exercise test was done, and at days 0, 4, 7, 14, and 28 neurocardiologic measurement sessions —heart rate and noninvasive baroreflex sensitivity, recumbent and tilt —were performed. Results: Interruption of training resulted in a significant and relevant decrease in the maximal oxygen uptake (from 65.7 ± 5.8 to 61.6 ± 4.7 mL O2·kg-1·min-1; P = 0.03), most likely associated with decreased competitive possibilities. Resting heart rate modestly increased (from 54.6 ± 7.2 to 58.8 ± 7.5 bpm), however, not significantly. Heart rate during 60° tilt increased considerably (from 70.1 ± 6.1 to 80.1 ± 9.1 bpm; P = 0.01), possibly due to a decrease in blood volume and an increase in cardiopulmonary baroreflex gain. Arterial baroreflex sensitivity decreased significantly in the recumbent (from 13.3 ± 5.4 to 9.8 ± 3.8 ms·mm Hg-1, P = 0.04), but not in the 60° tilt position (from 6.7 ± 2.0 to 6.0 ± 2.5 ms·mm Hg-1). The relative decrease in baroreflex sensitivity and maximal oxygen uptake correlated significantly (r = 0.71, P = 0.02). Conclusions: In summary, our data show that correlated detrimental changes in fitness and baroreflex sensitivity are measurable in these athletes after a month of interruption of training.